Within‐ and between‐patients associations between self‐efficacy, outcome expectation, and symptom change in cognitive behavioral therapy for generalized anxiety disorder. Issue 1 (4th July 2022) - Vîslă, Andreea; Allemand, Mathias; Flückiger, Christoph
Abstract: Objectives: There is limited information on how a change in patients' expectations over time results in symptom change in psychotherapy. This study aimed to investigate the changes in patients' expectations and symptoms during treatment and across follow‐up as well as to determine the within‐ and between‐patient relationships between two types of patient expectations, that is, self‐efficacy and outcome expectation, and symptom change. Methods: Participants (80 participants × 6 repeated measures; 480 observations) with generalized anxiety disorder were treated using cognitive behavioral therapy and the within‐ and between‐patient scores of self‐efficacy and outcome expectation were evaluated in multilevel models as predictors of symptom change. Results: Patients' self‐efficacy and outcome expectation increased, whereas severity of their symptoms reduced during and after treatment. At the within‐patient (WP) level, an increase in self‐efficacy was associated with a decrease in worry and depressive symptoms, and an increase in outcome expectation was associated with a decrease in depressive symptoms. The between‐patient (BP) effect, however, was contrary to the WP effect, that is, self‐efficacy was positively correlated with worry and outcome expectation was positively correlated with depressive symptoms Conclusion: These results highlight the importance of disaggregating the WP variability from BP variability in psychotherapy process–outcome research as they exhibit different associations at the within‐ and between‐patient levels. Clinical Trial Registration: ClinicalTrial.gov (NCT03079336).